Control handling in real-time communication protocols. - Shionozaki, Atsushi (Computer communication review.)
In order to guarantee real-time services in a network architecture, resource reservation schemes seem most effective. In such protocols, dynamic protocol parameter control is necessary to support balanced quality of service for applications which are allocated the resources of the system, but timeliness of protocol control negotiation has never been emphasized.We have proposed RtP, a general purpose real-time protocol which supports virtual channels used exclusively for control information processing in an internet-work. However, our first proposal did not provide an effective mechanism for preallocating control channels thus presenting an overhead in gateways.This paper presents a simple new protocol for managing control reservations on each subnetwork of an internet; it is called the Virtual Control Setup Protocol (VCSP). It provides an interface between the network layer and the data link layer for ensuring the timeliness of control information. The effectiveness of VCSP is investigated and demonstrated by a prototype implementation.